Service Quality of Self-Checkout Technology in Malaysian Hypermarket: A Case Study in Johor - Siah, J.W.; Fam, S.F.; Prastyo, D.D.; Yanto, H.; Fam, K.S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The revolution of retailing has been transformed into a new era where technology and human meets. The modern retail environment offers a new kind of services to customer impressively. The purpose of this research is to examine service quality attributes on self-checkout technology and its influence on customer satisfaction and reuse intention. The survey items are adapted from previous literature, and a mall intercept survey via convenient sampling was employed. The findings from 176 data were analyzed using IBM-AMOS to test the hypotheses. Control has a positive significant result with service quality. Ease of use and enjoyment have a negative significant result with service quality while speed and reliability have an insignificant result. Service quality has a strong positive effect on customer satisfaction as well as customer satisfaction with reuse intention. Thus, retail developers could tackle the correct path to make more comprehensive strategies through retail technology innovation to meet customer demand.